2012
DOI: 10.20344/amp.1420
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism risk factors and practices of prophylaxis: ENDORSE study results in Portugal.

Abstract: Venous thromboembolism (VTE) risk assessment is a cornerstone for the achievement of best practices and outcomes. Epidemiologic data and practices related to venous thromboprophylaxis as considered by the global ENDORSE study, (Epidemiologic International Day for the Evaluation of Patients at Risk for Venous Thromboembolism in the Acute Hospital Care Setting), enrolled 68,183 patients from 32 countries, in which Portugal. Within ENDORSE, data from all participant countries analyzed to determine their risk of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…In 68.9%, inappropriate pharmacological prophylaxis was administered, leading to an increased risk of bleeding events and costs. This finding is consistent with other studies that have shown high use of prophylaxis in low-risk patients [ 7 , 13 ]. These results could reflect either a clinical judgment of real risks and, if so, a clinically correct decision or an incorrect risk assessment [ 7 , 13 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In 68.9%, inappropriate pharmacological prophylaxis was administered, leading to an increased risk of bleeding events and costs. This finding is consistent with other studies that have shown high use of prophylaxis in low-risk patients [ 7 , 13 ]. These results could reflect either a clinical judgment of real risks and, if so, a clinically correct decision or an incorrect risk assessment [ 7 , 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…Regarding surgical patients, the results were somewhat unsatisfactory. When compared to the ENDORSE study, we pinpoint a lower rate of patients under adequate prophylaxis (42.0% in our study versus 58.5% in the ENDORSE study), however, our results are far better than those from some international studies, like DissolVE-2, which reports a 10.3% rate of risk-patients receiving adequate prophylaxis [ 8 , 13 ]. In addition, the rate of patients undergoing inadequate prophylaxis was 58.0%, well above expectations, compared to other studies reporting rates inferior to 40.0% [ 13 ].…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations